Stress among students during MCO / Qistina Sarah Abdul Hafidz ... [et al.] - Abdul Hafidz, Qistina Sarah; Noorshahlin, Noor Fatinah Nadiah; Remy Khairil, Nur Fariha; Haridatul Akmar, Nur Natasha (Faculty of Communication & Media Studies, 2021)
The struck of COVID-19 pandemic had affect education institutions such as kindergarten, schools and Universities in Malaysia to close during the Movement Control Order (MCO) period. Therefore, online class or Online Distance Learning (ODL) is another alternative used by education institutions to continue its syllabus. The application of ODL during MCO had affect students in terms of stress. Therefore, researchers have identified the factors that contribute to stress and the consequences of stress among students. For the methodology of this research, the researchers follow the research design of qualitative method. Next, the unit analysis of this research is individual. It is because researchers interviewed eight different students from various universities in Malaysia. The type of interview applied in this research is structured interview. The researchers conducted the interview online using the virtual platform such as Skype, Whatsapp video call and Facetime. Moreover, the researchers used two different sampling method to choose the interviewees. Next, researchers used thematic analysis to analyze data that was recorded after the interview sessions. The data from interview are kept as transcript and references. From the findings, researchers succeeded in identifying the factors of stress and the consequences of stress during MCO. Most of the interviewee gave their opinion but with similar answers. In conclusion, MCO is a great alternative to break the COVID-19 chain but also a challenge to students around the world.